INOVASI TEKNOLOGI LORA DALAM SISTEM PEMANTAUAN KUALITAS AIR SUNGAI UNTUK MENDUKUNG PERTUMBUHAN BUDIDAYA TAMBAK IKAN YANG BERKELANJUTAN - Danial, Mochammad Meddy; Imansyah, Fitri; Sujana, Ivan (Universitas Mataram, 2024)
Sungai Itik Village, as a rural community that relies on fish farming as its main livelihood, is faced with significant challenges related to monitoring river water quality, which is the main water source for fish farming activities. This activity aims to investigate the application of LoRa technology innovation in a river water quality monitoring system to support the sustainable growth of fish pond cultivation in Sungai Itik Village. Through the development of a LoRa-based information system, we have succeeded in integrating water quality sensors that are sensitive to important parameters such as pH, temperature, dissolved oxygen and water turbidity levels. Data obtained in real-time from these sensors is uploaded to a cloud platform, enabling continuous and accurate monitoring of river water quality. The implementation of this system has provided significant benefits for the people of Sungai Itik Village. This tool can quickly respond to changes in water quality that can affect fish health and pond productivity. Apart from that, this system also helps in making the right decisions regarding sustainable management of fish pond cultivation. The results of this activity show that LoRa technological innovation in monitoring river water quality has great potential to increase the sustainability of fish pond cultivation in rural communities such as Sungai Itik Village. The implications of this activity can also be widely applied in the context of fisheries farming in areas with similar challenges.